Factors Contributing to Stunting in Indonesia: A Review - Amud Sunarya; Thaha, Abdurrahman Rahim; Yandes, Jufri; Juniadi, Dedy; Akbar, Yonarisman Muhammad; Nugroho, Sapto Setyo (Politeia : Journal of Public Administration and Political Science and International Relations, 2024)
Stunting prevalence in Indonesia has exhibited a relatively consistent trend, with rates of 36.8% in 2007, 35.6% in 2010, and a slight increase to 37.2% in 2013, though showing a decline to 30.8% in 2018. Despite this decrease, Indonesia's stunting rates remain higher than the global prevalence of 22.2%, indicating a significant public health concern. Stunting poses long-term health risks, and early prevention is crucial. This article review aims to identify factors contributing to child stunting in Indonesia, utilizing the WHO's conceptual framework. Employing various study designs and extensive literature search, the review identified 15 relevant articles, highlighting factors like exclusive breastfeeding, household economic status, maternal education, and environmental conditions as key determinants of child stunting.